Relationship between blood antioxidant paraoxonase-1 and the offspring yield in Hair goats - S. Dursun (Bulgarian Journal of Veterinary Medicine)
Small ruminants bring unproductive pastures to the economy with products such as meat and milk. Although the management of Hair goats is difficult compared to that of sheep, they make better use of unproductive pastures than sheep. The birth rate of Hair goats is high, but the multiple birth rate is quite low. This study aimed to determine the relationship between the antioxidant paraoxonase-1 (PON-1), and the offspring yield in Hair goats. In the second week of September, 100 females were randomly selected and blood samples were taken 15 days before the introduction of male goats to the herd from both males and females. Blood was taken from the same animals again before starting milk-ing in May. Paraoxonase-1 values were found to be low and significantly different in both sexes in October compared to May. There was a statistical difference (P≤0.05) in PON-1 level in terms of gender and birth type. The PON-1 level of Hair goats that gave birth to twins was like that of male goats and goats with single birth, while it was insignificant between single-birth and infertile goats. It was found that a low PON-1 value was associated with low fertility whereas twin births were closely related to high value of PON-1. PON-1 was found to be important for multiple births (P≤0.05). As a result, it was concluded that the PON-1 level increased the birth rate and offspring yield in Hair goats.